THE PERFORMANCE ON USING CONJUNCTION BY THE FIFTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Mita; Eny Syatriana; Ilmiah (Journal of Language Testing and Assessment, 2021)
This study aimed at finding out: 1. How are the students’ performance on the use of coordinating conjunction, 2. how are the students performance on the use subordinating conjunction. The method in this research was descriptive quantitative, the reseacher chooses subject class C by the fifth-semenster studnets of English Department from Muhammadiyah University of Makassar, consisting of twenty students. To got the data of this research were collected through tests and interviews by google form.The test results from students, that students know better the use of coordinating conjunction, many students answer correctly with an average highest score of 670, but the students difficult to distinguish the use of conjunction which has the same meaning, like but and yet, also for and because. for subordinating conjunction. shows, the students low understand the use of that conjunctions, many students answer incorrectly, expecially conjunction althogh, after and where. an average highest score of 605, the students still confused the function of that conjunction itself.